The Symbolic Meaning of the Lemon Basidakah Tradition in Nagari Kinari, Bukit Sundi District, Solok Regency, West Sumatra Province - Rahmawati, Mila; Yulika, Febri (Kirana Publisher (KNPub), 2025)
This research is entitled